Progress of research on personalized health management and education for patients with tinnitus and hearing loss (耳鸣伴听力下降患者个性化健康管理教育研究现状) - ZHAO Tangying (赵堂英); ZHAO Ruiqian (赵瑞倩); YU Weixiu (于维秀) (中西医结合护理)
Tinnitus, often associated with hearing loss, may be associated with lower health related quality of life. This paper reviewed the studies on personalized health management and education for patients with tinnitus and hearing loss in perspectives of health assessment, health guidance and health education methods, and provided reference for perfecting the strategy of clinical health education. (耳鸣伴听力下降严重影响患者生活质量。本研究从耳鸣伴听力下降患者的个性化健康评估、个性化健康指导、健康教育方法等方面进行总结和阐述, 旨在为临床进一步完善个性化健康管理教育策略提供参考。)